Laboratory testing for evaluating performance of the residue in the environment - Eyo, Catherine Kai Ling (Nanyang Technological University, 2022)
This study is to explore the shear wave velocity of incineration bottom ash residue in the environment through cyclic triaxial testing. The bender element is used to transmit and received the S-wave which travels through the sample. Both dry and saturated test are used in the cyclic triaxial test stage. The results of the two samples are obtained for shear wave velocity. The results suggest that shear wave velocity for dry test is higher than saturated test, as according to literature review of previous tests done on saturation. The peak-to-peak values and start-to-start values were also explored and compared, showing that both values can be used in lieu of each other. Concurrently, the first sample of incineration bottom ash has a higher shear wave velocity compared to the second sample of incineration bottom ash. This shows that the first sample has higher chance of being used in construction due to its higher subgrade strength and capable to withstand higher seismic movements.